The Effect of Pair Training on the Underhand Passing Ability of Students at SMA Negeri 5 Palopo - St Hadijah; Ahmad Ahmad; Suaib Nur (Universitas Hamzanwadi, 2026)
This study was motivated by the low underhand passing skills of volleyball extracurricular students at SMA Negeri 5 Palopo, as evident from the unsatisfactory results of inter-school tournaments. The purpose of this study was to determine the effect of paired training on students' underhand passing skills. This study used an experimental method with a one-group pretest-posttest design. The research population consisted of all 30 students participating in the volleyball extracurricular activity, with a sample of 15 students selected using purposive sampling. The research instrument used a passing skill test with a scoring system based on ball direction accuracy. The treatment consisted of a paired training program conducted over 16 sessions with a training frequency of three times per week. Data analysis techniques included descriptive analysis, normality test, homogeneity test, and hypothesis testing using a paired sample t-test at a significance level of α = 0.05. The results showed that paired practice had a significant effect on improving students' underhand passing skills. The average pretest score of 12.60 increased to 21.00 on the posttest, with an increase of 8.40 points. The hypothesis test results obtained a t-count value of 14.000 > t-table 2.145 and a significance value of 0.000 < 0.05. The discussion revealed that the effectiveness of paired practice was due to direct feedback, repeated technical corrections, and the creation of an interactive and collaborative learning environment. The conclusion of this study is that there is a significant effect of paired practice on improving the underhand passing skills of students at SMA Negeri 5 Palopo. Paired practice is recommended as an alternative method in teaching basic volleyball skills at the high school level.